Analysis of Insya Thalabi in the Maulid al-Dibai’ by Imam Abd al-Rahman al-Diba'i: Types and Meanings | Tahlīl al-Insyā al-Thalabī fī Kitāb Maulid Al-Dība’ī lil Imām ‘Abd Al-Rahmān bin ‘Alī bin Muhammad bin ‘Abdullah Al-Diba’i: Anwā’uhu wa Ma’ānīhi - Zaid, Abdul Hafid; Mustofa, Yusuf Aziz; Arifin, Syamsul (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2024)
This study explores the use of Insya Thalabi in Maulid al-Dība’ī by Imam Abd al-Rahman al-Dība’ī. This renowned classical Arabic text narrates the life of the Prophet Muhammad (PBUH) and is widely read by Muslims. The book holds significant literary value, incorporating rich historical elements and stories in its prose and poetry. The research aims to identify the types of Insya Thalabi and reveal their meanings within the context of Maulid al-Dība’ī. This study using a qualitative, descriptive-analytical library research approach, the study identifies 104 occurrences of Insya Thalabi, categorized as follows: 45 instances of Amr, 2 of Nahy, 7 of Istifham (interrogative), 5 of Tamany, and 45 of Nida. The study further reveals the meanings associated with these instances, with 45 meanings for Amr, 2 for Nahy, 7 for Istifham, 5 for Tamany, and 45 for Nida. These findings highlight the diverse functions of Insya Thalabi in enriching the text’s literary and historical content. The implications of this research suggest that Insya Thalabi plays a significant role in enhancing the clarity and emotional expression of the narrative. Future studies could explore the comparative use of Insya Thalabi in other classical Arabic texts and investigate its impact on modern Arabic literary analysis.